(3cJGH GdHdHd aj CUhd Gdabgs - (3fLe GdOjf SdjeGf Hf YHO GdWhai GdMfHdis; (3GHf bOGegs ((3eMeO Hf YHO Gddg Hf MejO GdMfHdi s)
(3ChdgG (B:s
(3bGd GdTjN fLe GdOjf SdjeGf Hf YHO GdWhai GdMfHdi CUhd Gdabg COdJg adfJcde YdjgG CUdkG CUd HYO PcQ ebOeI JTJed Ydi aUhd GdChdi ai JYQa GUhd Gdabg s
(3BNQgG (B:s
(3hbO MUd HgPG HjGf GdQLMGf efg Lgg GdbQGFf hhLg LMGf ai CcKQ gPg GdJQLMGJ Hjf adgPG CgedfG PcQg ENJUGQkG hGdgd JYGdi GYed hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3HChdg Jedc HGSe CHj HcQ Hf eMeO NhbjQ Gdeci GdMfHdi GdcdHi SfI (B1310 (3g`s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3Gdabg GdMfHdjs